Implementing an educational program to increase preoperative screening for obstructive sleep apnea using the stop-bang questionnaire - Davies, Adam; W. Patrick, Monaghan; Gerard, Hogan (International Journal of Advanced Nursing Studies, 2016)
Background: Obstructive sleep apnea (OSA) is a potentially fatal disease process that has been linked to higher rates of morbidity and mortality as well as increased perioperative complications. OSA is characterized by repetitive pauses in breathing during sleep. Greater than 92% of women and 82% of men who are plagued by moderate to severe sleep apnea are undiagnosed and may go unrecognized in the perioperative setting. The gap between a high prevalence of undiagnosed OSA in the adult population and the low level of clinical recognition has been well-documented. The term â€œSTOP-BANGâ€ is an acronym for eight independent elements predictive of OSAâ€”three are OSA-related symptoms, three are physiological measurements, and two are patient characteristics.Methods: This project used a quasi-experimental design using a 16-question self-developed survey based on the technology acceptance model (TAM). Participants were asked to read an educational pamphlet on OSA and then complete the survey.Results: This study found strong evidence to suggest that among Certified Registered Nurse Anesthetists (CRNAs) and Student Registered Nurse Anesthetists (SRNAs), those with higher scores on Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Attitude toward Use (AT), tend to have a higher Behavioral Intention to Use (BIU) the STOP-BANG screening tool.Conclusions: The results suggest that programs targeted at raising CRNAsâ€™ and SRNAsâ€™ PEOU, PU, and AT regarding the STOP-BANG questionnaire will culminate in increased use of the STOP-BANG screening tool. The use of this screening tool will detect patients previously unidentified as having OSA, and ultimately prevent perioperative complications associated with this disease.